ASSESSING AND MODELING THE DETERMINANTS OF HOUSEHOLD WATER CONSUMPTION IN LOKOJA TOWN, KOGI STATE (FUDMA JOURNAL OF SCIENCES, 2023)
Water is a scarce resource especially in Nigeria where water shortage is experienced in most of the cities. Determinants of domestic water consumption and their significance vary from place to place. This study analyzed sources and consumption of domestic water supply and investigating the determining factors of domestic water consumption in Lokoja. Data was collecting using the systematic random sampling method. 236 households were sampled and analysed using SPSS software. The results showed that 61.4% of the households got pipe borne water supply, 9% used well water, 9.3% used water from the River Niger and 20.3% got water supply through mechanized boreholes. Household water consumption vary from 121.50 litres/H/d to 2546.50 litres/h/d. The regression analysis has the model Y= 634.786 + 56.492 SE + 22.075AG + 7.428MA + 50.938EDU + 3.973OC+ 102.750MS + 135.585HS. The result of the multiple linear regression analysis indicated that such factors like size of household, level of education, age, sex and monthly income of households strongly determined household water consumption in Lokoja. The multiple correlation coefficient in R= 0.761 indicates that 76.1% of all tested variables correlated positively with domestic water consumption. This study concluded that even though more than half of the population have access to piped water, majority of people in the densely populated areas rely on other sources of water. This study recommends that Kogi State Water Board should take measures for expanding the network of government administered water supply to meet household water demand.
Keywords: water sources, domestic water consumption, regression model